UPAYA LEMBAGA PEMASYARAKATAN KELAS II A PEKANBARU DALAM MENGATASI OVERCROWDED DALAM MENCEGAH RESIDIVIS - Nahjatun Nahdiyah; Kasmanto Rinaldi (SEIKAT: Jurnal Ilmu Sosial, Politik dan Hukum, 2023)
Observations revealed that several problems related to prison overcrowding have the potential to be one of the driving factors for the birth of recidivists (study at Lapas Class II A Pekanbaru). This study aims to find out the efforts of the Pekanbaru Class II A Correctional Institution in dealing with overcrowding so as not to give birth to recidivists. This research uses the type or method of qualitative descriptive research. The author in this study took data sources from interviews conducted with several informants, namely the Head of the Pekanbaru Class II A Correctional Institution, the Pekanbaru Class II A Correctional Institution Officer, and the Pekanbaru Class II A Correctional Families. Based on research conducted on the efforts of Pekanbaru Class II A Penitentiary in overcoming overcrowding so as not to give birth to recidivists, it can be concluded that it consists of formal and informal forms, namely Formal consisting of Giving remissions to inmates, both ordinary prisoners and recidivists. Provide guidance in the form of personality development and independence development. Providing conditional leave opportunities for convicts to return to their families. Informal such as collaborating with other institutions and emphasizing recidivists.